The Next Infodemic: Abortion Misinformation - Sherry L Pagoto; Lindsay Palmer; Nate Horwitz-Willis (JMIR Publications, 2023)
The World Health Organization (WHO) defines an infodemic as the proliferation of false or misleading information that leads to confusion, mistrust in health authorities, and the rejection of public health recommendations. The devastating impacts of an infodemic on public health were felt during the COVID-19 pandemic. We are now on the precipice of another infodemic, this one regarding abortion. On June 24, 2022, the Supreme Court of the United States (SCOTUS) decision in Dobbs v. Jackson Women's Health Organization resulted in the reversal of Roe v. Wade, which had protected a woman's right to have an abortion for nearly 50 years. The reversal of Roe v. Wade has given way to an abortion infodemic that is being exacerbated by a confusing and rapidly changing legislative landscape, the proliferation of abortion disinformants on the web, lax efforts by social media companies to abate abortion misinformation, and proposed legislation that threatens to prohibit the distribution of evidence-based abortion information. The abortion infodemic threatens to worsen the detrimental effects of the Roe v. Wade reversal on maternal morbidity and mortality. It also comes with unique barriers to traditional abatement efforts. In this piece, we lay out these challenges and urgently call for a public health research agenda on the abortion infodemic to stimulate the development of evidence-based public health efforts to mitigate the impact of misinformation on the increased maternal morbidity and mortality that is expected to result from abortion restrictions, particularly among marginalized populations.